Isolation and identification of amylase, protease and lipase producing bacteria from soil of different area of Gujarat - Bhoomi Patel (International Journal of Pharma and Bio Sciences, 2020)
Enzymes are being used in numerous new applications in the food, feed, agriculture, paper, leather, and textiles industries, resulting in significant cost reductions. At the same time, rapid technological developments are now stimulating the chemistry and pharma industries to embrace enzyme technology, a trend strengthened by concerns regarding health, energy, raw materials, and the environment , hence are reusable. For these present study different samples of soil were collected from Banaskantha (Bhabhar), Rajkot (Safar), Ahmedabad (Shilej), Surat (Chikhali), Sabarkatha (Palanpur) Gujarat India. The samples were serially diluted and inoculated on Nutrient agar by spread plate technique. The isolated bacteria were morphological and biochemical characterized and Gram’s staining was performed using Gram’s reagents (Hi-Media kit) and studied its metabolic activities by performing different biochemical tests. Bacteria were identified for amylase, protease and lipase activities using starch agar-1%, casein agar-1% and tributyrin agar-1% respectively. Isolate Strains could be compared with the previously found strains Bacillus cereus ATCC 1305, 5610, 1458 for the optimum production of amylase, protease and lipase.